Macropinocytosis: A Metabolic Adaptation to Nutrient Stress in Cancer - Recouvreux, Maria Victoria; Commisso, Cosimo (Frontiers in Endocrinology, 2017)
Oncogenic mutations, such as Ras mutations, drive not only enhanced proliferation, but also the metabolic adaptations that confer to cancer cells the ability to sustain cell growth in a harsh tumor microenvironment. These adaptations might represent metabolic vulnerabilities that can be exploited to develop novel and more efficient cancer therapies. Macropinocytosis is an evolutionarily conserved endocytic pathway that permits the internalization of extracellular fluid via large endocytic vesicles known as macropinosomes. Recently, macropinocytosis has been determined to function as a nutrient-scavenging pathway in Ras-driven cancer cells. Macropinocytic uptake of extracellular proteins, and their further degradation within endolysosomes, provides the much-needed amino acids that fuel cancer cell metabolism and tumor growth. We review here the molecular mechanisms that govern the process of macropinocytosis, as well as discuss recent work that provides evidence of the important role of macropinocytosis as a nutrient supply pathway in cancer cells.